2013
DOI: 10.1007/s11434-013-5793-3
|View full text |Cite
|
Sign up to set email alerts
|

Vocalization during copulation behavior in greater horseshoe bats, Rhinolophus ferrumequinum

Abstract: Vocal communication plays an important role for individual recognition and male-female interaction during mating in greater horseshoe bats, especially in respect to mate fidelity, which ensures that the bats can maintain a stable social organization. Few studies, however, have addressed the calling behavior during copulating in bats. Here, we initially report the copulation vocalizations and behaviors of both male and female greater horseshoe bats. During copulation, the male assumed a dorsal position and arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…Although there have been studies on sexual dimorphism of bat communication sounds (Kanwal et al 1994;Liu et al 2013;Ma et al 2006), many studies have been mainly focused on the sexual dimorphism of orientation pulses in the CF-FM bat by analyzing the predominant CF (Jones et al 1992Knörnschild et al 2012;Russo et al 2001;Feng et al 2003;Siemers et al 2005;Suga et al 1987). In the present study, we have clearly shown that sexual dimorphism of echolocation pulses in the CF-FM bat can also be found in other multiple pulse parameters.…”
Section: Parameterssupporting
confidence: 61%
“…Although there have been studies on sexual dimorphism of bat communication sounds (Kanwal et al 1994;Liu et al 2013;Ma et al 2006), many studies have been mainly focused on the sexual dimorphism of orientation pulses in the CF-FM bat by analyzing the predominant CF (Jones et al 1992Knörnschild et al 2012;Russo et al 2001;Feng et al 2003;Siemers et al 2005;Suga et al 1987). In the present study, we have clearly shown that sexual dimorphism of echolocation pulses in the CF-FM bat can also be found in other multiple pulse parameters.…”
Section: Parameterssupporting
confidence: 61%
“…Although it’s been shown that horseshoe bats have a rich communication repertoire (e.g. [32] ), recent work suggests that typical echolocation calls are used by males before copulation [33] , supporting the use of echolocation calls as stimuli presented to the tested animals. Previous work has demonstrated that R. mehelyi was able to recognize the gender of conspecifics from their calls only, providing evidence that cues on the gender of the emitter are encoded in echolocation signals [19] , hence we considered that the animals tested recognized acoustically the gender of the call emitter.…”
Section: Methodsmentioning
confidence: 93%
“…, ; Sachteleben & von Helversen, ; Jahelková & Horáček, ; Liu et al. ). For mammals in general, behavioral functions of the baculum have also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In all three species the mating systems have been described as resource defense polygyny with seasonal single-male multi-female groups, but it seems to be more complicated and might share traits with a lek-based mating system (Sachteleben & von Helversen, 2006; Jahelkov a & Hor a cek, 2011). However, in bats very little is known about mating behavior, copulation duration, or copulation postures (Glass, 1966;Barclay & Thomas, 1979;O'Brien & Nankervis, 1994;Hosken et al 2001;Dixson et al 2004Dixson et al , 2012Sachteleben & von Helversen, 2006;Jahelkov a & Hor a cek, 2011;Liu et al 2013). For mammals in general, behavioral functions of the baculum have also been proposed.…”
Section: Introductionmentioning
confidence: 99%